The Integrationist Alternative to the Insanity Defense: Reflections on the Exculpatory Scope of Mental Illness in the Wake of the Andrea Yates Trial - Slobogin, Christopher (2003)
On June 20, 2001, Andrea Yates took the lives of her five children by drowning them, one by one, in a bathtub. At her trial on capital murder charges nine months later, she pleaded insanity. Despite very credible evidence that she had long suffered from serious mental disorder, a Texas jury convicted Yates of murder and sentenced her to life in prison. Her tragic and controversial case led many to question whether the so-called M'Naghten test for insanity, which forms the basis for the insanity defense in Texas, adequately defines the exculpatory effect of mental disorder. This article is based on a talk given at a conference entitled The Affirmative Defense of Insanity in Texas, which took place in the wake of the Yates trial